(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Polycystic ovary syndrome (PCOS) is the most common and treatable endocrine dysfunction in fertile women. The pathophysiology of PCOS involves primary defects in the hypothalamic–pituitary axis, insulin secretion and action, and ovarian function.Studies show 20-40 percent of female first-degree relatives of women with PCOS also have the syndrome.Genetic studies have identified a link between PCOS and disordered insulin metabolism and hyperinsulinemia.PCOS is characterized by hyperandrogenism, irregular ovulatory cycle and metabolic derangement, including glucose intolerance and hyperinsulinemia. Hyperandrogenism is a clinical hallmark of PCOS.In women with PCOS, Ovulation problems are usually the primary cause of infertility. PCOS is the most common cause of anovulatory infertility; ∼ 90–95% of women seeking treatment for infertility have PCOS. PCOS may cause higher risk for infertility, type 2 diabetes, high blood pressure, and endometrial cancer. The most common symptoms are irregular period, weight gain, acne, and excessive facial and body hair. PCOS has no cure but there are multiple treatments that can reduce symptoms. Life style modification includingdiet and exercise, have shown a positive influence on women with PCOS. J Bangladesh Coll Phys Surg 2021; 39(1): 53-58